Migration of Wintering Grey Plover From Southeast Asia to North‐Central Siberia Challenges Breeding Population Delineations in Russia - David Li; Max De Yuan Khoo; Richard B. Lanctot; Pavel S. Tomkovich; Zhijun Ma; Jun Rui Chow; Malcolm Chu Keong Soh; Shufen Yang; Choon Beng How; Adrian Loo; Robert Teo; Liang Jim Lim; et al. (Ecology and Evolution, 2025)
ABSTRACT Shorebird populations are declining across the world due to factors such as habitat loss and climate change. Identification of shorebird migration routes and important stopover sites can facilitate the implementation of strategic and effective conservation measures. Using a satellite transmitter, we successfully tracked the migration of one Grey Plover (Pluvialis squatarola) from its wintering grounds in Singapore north along the East Asian‐Australasian Flyway (EAAF) to its breeding grounds located east of the Taymyr Peninsula in north‐central Siberia. This provides the first evidence that the Singapore plover could be part of the Yamal/Taymyr population that is known to only migrate south via the East Atlantic Flyway and winter in Western Europe. After breeding, the bird took an unexpected westward migration towards northwestern Taymyr Peninsula where it stopped at two locations for 9 and 5 days, respectively, before migrating south through Central Asia. Prior to crossing the Himalayan mountains, however, the plover migrated east again from the Xinjiang Autonomous Region in northwest China to Jiangsu Province along the Yellow Sea, before turning south again to migrate along the EAAF to return to its wintering ground in Singapore. The plover's westward post‐breeding migration was contrary to prevailing winds, while the eastward migration north of the Himalayas was facilitated by strong easterly winds. The plover's westward migration post‐breeding may be attributed to acquiring additional food resources prior to its southward migration, and/or because it was searching for future breeding or staging grounds. Both possibilities may be associated with habitat changes occurring on their breeding grounds due to climate change. Further studies on the Grey Plovers wintering in Southeast Asia are needed to understand whether the migration route taken by this individual is representative of the species.